Study of the Long-Term Results of Decompressive Craniectomy after Severe Traumatic Brain Injury Based on a Series of 60 Consecutive Cases - Gaétane Gouello; Olivier Hamel; Karim Asehnoune; Eric Bord; Roger Robert; Kevin Buffenoir (The Scientific World Journal)
Background. Decompressive craniectomy can be proposed in the management of severe traumatic brain injury. Current studies report mixed results, preventing any clear conclusions on the place of decompressive craniectomy in traumatology. Methods. The objective of this retrospective study was to evaluate the results of all decompressive craniectomies performed between 2005 and 2011 for refractory intracranial hypertension after severe traumatic brain injury. Sixty patients were included. Clinical parameters (Glasgow scale, pupillary examination) and radiological findings (Marshall CT scale) were analysed. Complications, clinical outcome, and early and long-term Glasgow Outcome Scale (GOS) were evaluated after surgery. Finally, the predictive value of preoperative parameters to guide the clinician’s decision to perform craniectomy was studied. Results. Craniectomy was unilateral in 58 cases and the mean bone flap area was 100 cm2. Surgical complications were observed in 6.7% of cases. Mean followup was 30 months and a favourable outcome was obtained in 50% of cases. The initial Glasgow Scale was the only statistically significant predictive factor for long-term outcome. Conclusion. Despite the discordant results in the literature, this study demonstrates that decompressive craniectomy is useful for the management of refractory intracranial hypertension after severe traumatic brain injury.